A new optimization algorithm for solving wind turbine placement problem: Binary artificial algae algorithm - Beşkirli, Mehmet; Koç, İsmail; Haklı, Hüseyin; Kodaz, Halife (Renewable energy, 2018)
The wind turbine has grown out to be one of the most common renewable energy sources around the world in recent years. As wind energy becomes more important, the significance of wind turbine placement also increases. This study was intended to position the wind turbines on a wind farm to achieve the highest performance possible. The turbine placement operation was designed for a 2 km × 2 km area. The surface of the area was calculated by dividing it into a 10 × 10 grid and a 20 × 20 grid with the use of binary coding. The calculation revealed ten different new binary algorithms using ten different transfer functions of the Artificial Algae Algorithm (AAA) that has been successfully applied to solve continuous optimization problems. These algorithms were applied to the turbine placement problem, and the algorithm that obtained the best result was called the Binary Artificial Algorithm (BinAAA). The results of the proposed algorithm for the binary turbine placement optimization problem were compared with those of other well-known algorithms in the relevant literature. The algorithm that was proposed in the study is an efficient algorithm for the placement problem of wind turbines since it optimized the binary search space and achieved the most successful result. •A new optimization algorithm was proposed based on the artificial algae algorithm (AAA).•The proposed method was used to solve binary wind turbine placement problem.•The performance of the turbine placement was analyzed by using two different grid structures of 10 × 10 and 20 × 20.•The performance of the BinAAA was compared to GA, MILP, BPSO and Lazy Greedy algorithms.